Board Acitivity and Firm Performance: Astudy of Financial Institutions in Kenya - Nebert Ombajo Mandala (European Scientific Journal, ESJ, 2019)
The research set out to determine whether board activity impacts institutional performance. Secondary data for a ten-year period between 2006 to 2015 from 98 sampled institutions from the financial sector was collected and analysed. The study adopted stratified sampling to ensure that all the categories of financial institutions were included in the sample. Analysis of the data was done by multiple regression analysis and generalized estimating equations. The study was anchored on several theories among them; the agency theory, stakeholder theory, and resource dependence theory. The findings are that board activity operationalised as the number of board meetings, significantly affect institutional performance. Additionally, the results further show that there exists an optimal number of board of director meetings with a statistical significant impact on institutional performance. 11 to 15 board of directors’ meetings annualy were found to optimize institutional performance. The research findings will aid in managerial policy formulation and managerial practice that promote better governance practices hence leading to enhanced institutional performance.